Co-occurrence of Metachromatic Leukodystrophy in Phelan-McDermid Syndrome. (February 2021) - Mingbunjerdsuk, Dararat; Wong, Melissa; Bozarth, Xiuhua; Sun, Angela
Phelan-McDermid syndrome or 22q13.3 deletion syndrome is a rare neurodevelopmental disorder characterized by neonatal hypotonia, severe speech delay, moderate to profound intellectual disability, and minor dysmorphic features. Regression of developmental milestones is often recognized as characteristic of this syndrome. We report a 6-year-old patient with Phelan-McDermid syndrome who presented with rapid neurologic deterioration secondary to metachromatic leukodystrophy due to a mutation of the arylsulfatase A gene ( ARSA ) on the other allele of 22q13.3. Metachromatic leukodystrophy was diagnosed later after clinical deterioration. Currently, there are no guidelines for screening Phelan-McDermid syndrome patients for metachromatic leukodystrophy. We propose screening for urine sulfatides at the time of Phelan-McDermid syndrome diagnosis to identify patients with pre-symptomatic or early symptomatic metachromatic leukodystrophy as it is important to facilitate discussion of treatment options and prognosis and provide medical surveillance for associated complications.